Enhancing women-focused investments in climate and disaster resilience. - Asian Development Bank. ([Manila] Asian Development Bank, 2020)
This publication explores why targeted investments in women are crucial to increase resilience to climate change and disasters and to achieve broader sustainable development.
Keywords: Climate change mitigation -- International cooperation; Climate change mitigation -- Moral and ethical aspects; Electronic books